Penerapan Teknik Analytical Hierarchi Process (AHP) Dalam Penentuan Probabilitas dan Dampak Risiko Pada Lembaga Amil Zakat di Kabupaten Gresik - Ersandhi Primanatara; Fatin Fadhilah Hasib (Universitas Airlangga, 2017)
Analysis Determination Of Probability And Risk Impact On LembagaAmil Zakat inGresik By Using Analytical Hierarchi Process (AHP) Techniques.From this research showed: 1) the criteria of reputation risk and loss probabilities muzaki are criteria that most frequently occur, while operational risk criteria are criteria that have the most impact happen; 2) Subcriteria of reputation risk and loss of muzaki the probability most common is the lack of support from regional leaders , while the sub-criteria that have the most impact if there is also the risk of lack of support from regional leaders; 3) Sub criteria for operational risk probability is the most common risk mustahik recruitment, while the sub-criteria that have the most impact if there is also a risk of recruitment mustahik; 4) Sub-risk criteria that have a probability distribution of the most common is muzaki want zakat funds channeled to the area where he lives, while the sub-criteria that have the most impact if there is a risk of the target complement mustahik.he use of other analytical techniques are highly recommended for further research to obtain significant values of the risks that occur in amil zakat institutions, sothat it can be seen also injurious.